OPTIMIZATION STUDY OF VISUAL COMFORT AND DAYLIGHT AVAILABILITY AT CADL ITB (DIMENSI: Journal of Architecture and Built Environment, 2016)
One way to reduce energy consumption in buildings is to use daylighting. However, daylight can cause visual discomfort in the form of glare. Center of Art, Design, and Language (CADL) Institut Teknologi Bandung is a building that has windows on west and east facades, so the probability of glare occurrence is high. In this research, CADL was optimized so that the percentage of time that Daylight Glare Probability below 0.21 (%DGP